Formation of Aesthetical Attitude to Nature as Necessary Part of Ecological Education - Kotlyarchuk, Hanna (Pedagogical Discourse, 2012)
The effectiveness of ecological education under the condition of formation of aesthetical attitude to nature is analyzed in the article. The importance of pedagogical influence in the process of study and upbringing onto the formation of ecological culture of pupils, and aesthetical attitude to nature is studied.